Local hydrological gradients structure high intraspecific variability in plant hydraulic traits in two dominant central Amazonian tree species. (21st September 2021) - Garcia, Maquelle N; Hu, Jia; Domingues, Tomas F; Groenendijk, Peter; Oliveira, Rafael S; Costa, Flávia R C
Abstract: Addressing the intraspecific variability of functional traits helps understand how climate change might influence the distribution of organismal traits across environments, but this is notably understudied in the Amazon, especially for plant hydraulic traits commonly used to project drought responses. We quantified the intraspecific trait variability of leaf mass per area, wood density, and xylem embolism resistance for two dominant central Amazonian tree species, along gradients of water and light availability, while accounting for tree age and height. Intraspecific variability in hydraulic traits was high, with within-species variability comparable to the whole-community variation. Hydraulic trait variation was modulated mostly by the hydrological environment, with higher embolism resistance of trees growing on deep-water-table plateaus compared with shallow-water-table valleys. Intraspecific variability of leaf mass per area and wood density was mostly modulated by intrinsic factors and light. The different environmental and intrinsic drivers of variation among and within individuals lead to an uncoupled coordination among carbon acquisition/conservation and water-use traits. Our findings suggest multivariate ecological strategies driving tropical tree distributions even within species, and reflect differential within-population sensitivities along environmental gradients. Therefore, intraspecific trait variability must be considered for accurate predictions of the responses of tropical forests to climate change. Abstract : Amazonian tree species have high intraspecific trait variability. Despite this variability, species function differently from each other. The high intraspecific trait variability suggests high population-level resilience to climate change.